Agnostic Identification for Growth Regimes - Carrillo Maldonado , Paúl (2021)
This study introduces the agnostic SVAR in the debate on growth regimes in the Post-Keynesian literature. This study contributes to the literature by presenting an agnostic identification method to determine the effect of the functional distribution on output and components of demand. To understand the identification in the aggregative method, the different endogeneities of the distribution are discussed. The analysis of Latin American countries between 1960–2014 also adds to the literature. Other authors include these economies in their studies, but not as the central part of their research, instead as one more country in the overall sample. The current study focuses only on the Latin American region.